A feasibility randomised controlled trial of the DECIDE intervention: Dementia carers making informed decisions - Kathryn Lord; Gill Livingston; Claudia Cooper (BJPsych Open, 2017)
Family carers report high levels of decisional conflict when deciding whether their relative with dementia can continue to be cared for in their own home. We tested, in a feasibility randomised controlled trial, the first decision aid (the DECIDE manual) aiming to reduce such conflict. Twenty family carers received the DECIDE intervention, and 21 received usual treatment. The intervention group had reduced decisional conflict compared with controls (mean difference −11.96, 95% confidence interval −20.10 to −3.83, P=0.005). All carers receiving the intervention completed and valued it, despite some still reporting difficulties with family conflict and problems negotiating services.